Impact of oncorhynchus mykiss, salmo trutta and clarias gariepinus on aquatic communities within Magoebaskloef Area, Limpopo Province, South Africa - Hlungwani, Hlulani Archebold (University of Limpopo, 2016)
Fish assemblages in relation to environmental variables within the Broederstroom and Debengeni Rivers were investigated. Both rivers were characterized by coarse substrates (pebble and gravel), temperatures below 20°C and moderate depth. Trout dominated fish assemblages in terms of numbers caught and was only distributed at higher altitude sites >1400 m (a.s.l). Coarse substrates, temperatures below 15°C, flow rate, depth and riparian cover were the variables shown important for the distribution of trout by multivariate analysis. The confinement of the trout to higher altitude and lack of optimal habitat variables at lower altitude sites contributed to the assertion that the area is marginal for trout distribution. It was therefore inferred that the marginality of the area is the possible explanation for trout failure to self-sustain its population, therefore dependent on the continuous restocks by the local hatchery. The continuous restocks of small size trout in the Broederstroom River prompted a subsequent study where trout’s impact on macroinvertebrate communities was evaluated through surveys and field experiments. The ability of small trout to utilize macroinvertebrates made them suitable candidates to evaluating their impact in the area. Aquatic invertebrates were found to be the main food source for the trout in the area. Taxa such as Gomphidae and Potamonautidae were the most frequent food items from the analyzed stomachs of trout. However, observations from both field surveys and experiments showed that trout is a weak regulator of macroinvertebrate diversity in the area, since there were no significant differences (ANOVA, P<0.05) in the diversity of invertebrates from trout invaded and uninvaded sites. Trout being a weak regulator of macroinvertebrate diversity in the area, it prompted surveys to the Ebenezer Dam to determine its competitive interactions with native predatory species. If the introduced species is a more efficient predator than the native predator species, it may affect changes in the structure of the habitat and food resource. Trout in the Ebenezer Dam was found to be selective to habitat variables whilst C. gariepinus was cosmopolitan to all habitat categories. The catfish also had a broader food preference than trout and the diversity of the food items was significantly different (ANOVA, P<0.05) between the two species. Unfortunately, the interspecific food overlap between trout and the catfish could not be determined in Ebenezer Dam, because of the small sample size of trout but food selection between vii them was evident. It was then concluded that the native catfish has a wider niche and it is a more efficient predator than the introduced trout. This observation contributed further to the assertion that the area is marginal for trout to thrive. Due to trout selection of habitat variables, it became prudent to carry out another study where the past climate and land use changes were analyzed to determine their effect on the habitat that could have affected the distribution of trout in the area. Future projections were also made to determine possible future impacts of climate change on the distribution of trout in the area. The effects of climate and land use change resulted in warmer water temperature, altered riparian cover and altered stream flow patterns. The changes could have influenced the confinement of trout to higher altitude catchments. The projected maximum temperatures by 2050 shows an increase from 2014 with a decline in precipitation. If these projections are to be the same for water temperature and flow regimes, coupled with current land uses in the area, they will continue to affect the distribution of trout negatively.
Thesis (M. Sc. (Agriculture)) -- University of Limpopo, 2016
Keywords: Oncorhynchus; Salmo trutta; Clarias gariepinus; Aquatic communities; Magoebaskloof area; Fish as food; Fish ecology